Integrated service delivery model in primary care to improve frailty in older Malaysians: Geko Integrated Service Delivery - Ahip, Sally Suriani; C., Y. Ting; Abdillah, M. A. B.; Y., J. Tan; Sabri, S. A. B.; Theou, O.; Shariff Ghazali, S.; Visvanathan, R. (Serdi-Editions, 2024)
Background: This study aimed to evaluate the implementation stage of Malaysia’s GeKo-Integrated Service Delivery (ISD) model for frailty management in primary care and explore its effectiveness in improving frailty scores. Methods: The implementation stage of Malaysia’s first three GeKo-ISD clinics was assessed using the WHO-ICOPE (Integrated Care of the Older Persons) scorecard. This involved evaluating documents related to the GeKo services and conducting in-depth interviews with key informants identified from those documents. The efficacy of GeKo-ISD was assessed by documenting the change in mean frailty scores between baseline and 3 months post intervention, measured by the Pictorial Fit Frail Scale Malay Version (PFFS-M), in patients who received GeKo-ISD care from October 2022 to April 2023. Results: All three GeKo clinics achieved the sustaining implementation level, scoring a total of 50 out of 52. The paired t-test reported a significant reduction (p= 0.001) in the PFFS-M scores from baseline to 3 months after the GeKo-ISD intervention. The mean (SD) scores were 8.6 (4.6) at baseline and 7.0 (4.1) at 3 months post-intervention. Conclusion: GeKo-ISD is a comprehensive approach of integrated care for older people, leveraging existing public funded primary care infrastructure. It shows promise, was impacted by the pandemic but now, with support from the government, exists in 32 centers across one state in Malaysia.